2011
DOI: 10.1093/bja/aer358
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapies for postoperative nausea and vomiting, and pain

Abstract: Postoperative nausea and vomiting (PONV) and pain are two of the major concerns for patients presenting for surgery. The causes of PONV are multifactorial and can largely be categorized as patient risk factors, anaesthetic technique, and surgical procedure. Antiemetics work on several different receptor sites to prevent or treat PONV. This is probably why numerous studies have now demonstrated that using more than one antiemetic is usually more effective and results in fewer side-effects than simply increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
4
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(165 citation statements)
references
References 143 publications
(83 reference statements)
2
139
4
20
Order By: Relevance
“…25,26 Anxiolytics are avoided and a multimodal approach to postoperative nausea and vomiting is used. 27 A prophylactic dose of unfractionated or low molecular weight heparin is given to reduce risk of venous thromboembolism (VTE). 28 Intraoperatively, goal-directed fluid administration is used with esophageal Doppler or noninvasive hemodynamic monitoring devices, [29][30][31] and minimally invasive surgery is used whenever possible.…”
Section: Quality Improvement Programsmentioning
confidence: 99%
“…25,26 Anxiolytics are avoided and a multimodal approach to postoperative nausea and vomiting is used. 27 A prophylactic dose of unfractionated or low molecular weight heparin is given to reduce risk of venous thromboembolism (VTE). 28 Intraoperatively, goal-directed fluid administration is used with esophageal Doppler or noninvasive hemodynamic monitoring devices, [29][30][31] and minimally invasive surgery is used whenever possible.…”
Section: Quality Improvement Programsmentioning
confidence: 99%
“…Pulmonary complications are the most frequent complications seen after the operations performed under general anesthesia, caused by numerous factors summarized in Table 5, with an incidence of up to 50%; [3][4][5][6][7][8] majorly dependent to the impeded swallowing, traumatic discordance in pharyngeal structures, and alterations on the physiology of the gastrointestinal tract, [9][10][11][12][13][14] of which may last up to the postoperative 18 th hour. [15,16] Postoperative pulmonary complication incidence of our study was 18.7%, which revealed that male gender, smoking history, coexistence of COPD, and psychiatric complication occurrence were the factors associated with higher risk for post-thoracotomy pulmonary complication incidence; all in accordance with the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…For patients at moderate to high risk for PONV, regional anesthesia should be considered. If this is not possible or contraindicated and a general anesthesia is used, a multimodal approach that combines pharmacologic and nonpharmacological prophylaxis to minimize risk of PONV should be adopted [25,27].…”
Section: Duration Of Anesthesiamentioning
confidence: 99%